Nur dalam Perspektif Al-Ghazali - Khoirun Nisa'; Muhyidin (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2020)
Reading this character, it never ends. This figure who was born in the city of Thusi, has never escaped the study in the world of scientific studies. Namely Imam Ghozali. The type of research used in this research is library research, namely research carried out through collecting data or scientific writings aimed at the object of research or data collection that is library in nature, or studies carried out to solve a problem that is basically focused on on a critical and in-depth study of relevant library materials. As the 20th century Ghazalian Sulaiman Dunya once said about this figure” - in Tsaqafah Al-Ghazali - we will find in Imam Ghazali there are at least two madhabs; The